The effect of using multimedia in learning the skill of passing from the bottom of volleyball - Haneen Nabeel Dr. Huda Badawi (physical education and sport sciences college for women/ Baghdad University, 2020)
The aim of the research is to:. Preparation and implementation of special educational units using multimedia to learn the skill of scrolling from below. 2 to recognize the impact of the use of multimedia in learning the skill of scrolling from below. 3 to identify the differences between the tests after the two groups research in learning the skill of passing from the bottom volleyball. The research represented the students of the first stage and the sample of the research was drawn randomly and the number of (50) students were divided into two experimental and control groups and each group (25) students were used standardized tests and conducting pre-tests and the implementation of the main experiment in the application of multimedia in the form of educational units 8) Units of the skill of passing from the bottom and then were conducted after the tests using statistical means The third section included the presentation, analysis and discussion of the results were used statistical bag spss. The researcher reached:. The use of multimedia has a clear positive effect in learning the skill of scrolling from the bottom volleyball. The researcher recommends the following:. The need to conduct similar research on different samples and other games. The need to conduct similar research on different skills and for beginners.